A 15‐year overview of increasing tramadol utilisation and associated mortality and the impact of tramadol classification in the United Kingdom. Issue 5 (24th September 2017) - Chen, Teng‐Chou; Chen, Li‐Chia; Knaggs, Roger David
Abstract: Purpose: This study aimed to develop hypotheses to explain the increasing tramadol utilisation, evaluate the impact of tramadol classification, and explore the trend between tramadol utilisation and related deaths in the United Kingdom. Methods: This cross‐sectional study used individual patient data, the Clinical Practice Research Datalink from 1993 to 2015, to calculate monthly defined daily dose (DDD)/1000 registrants, monthly prevalence and incidence of tramadol users, annual supply days, and mean daily dose of tramadol. Aggregated‐level national statistics and reimbursement data from 2004 to 2015 were also used to quantify annual and monthly tramadol DDD/1000 inhabitants and rate of tramadol‐related deaths in England and Wales. Interrupted time‐series analysis was used to evaluate the impact of tramadol classification in June 2014. Results: Prevalence of tramadol users increased from 23 to 97.6/10 000 registrants from 2000 to 2015. Both annual dose and annual supply days of existing tramadol users were higher than new users. Level and trend of monthly utilisation (β2 : −12.9, β3 : −1.6) and prevalence of tramadol users (β2 : −6.4, β3 : −0.37) significantly reduced after classification. Both annual tramadol utilisation and rate of tramadol‐related deaths increased before tramadol classification and decreased thereafter. Conclusions: Increasing tramadol utilisation was influenced by the increase in prevalence and incidence of tramadol users, mean daily dose, and day of supply. Prevalence of tramadol users, tramadol utilisation, and reported deaths declined after tramadol classification. Future studies need to evaluate the influencing factors to ensure the safety of long‐term tramadol use.